DEPRESSION IN PREGNANCY - CONSEQUENCES AND TREATMENT MODALITIES - Mp, Divya; Rabbani, Syed Imam; G., Mrudula (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Depression is a mood disorder which can affect 1 in every 4 women at some point of life even during pregnancy. Depression is most often not properly diagnosed during pregnancy as it is assumed by people to be just another type of imbalance in hormones. But this assumption can be very dangerous to the mother and the fetus. The health care professionals are very cautious about the treatment for depression in pregnancy as both uses of antidepressant and untreated depression in pregnancy can lead to risks for the unborn baby. This review focuses on the complications associated with both treated and untreated depression during pregnancy. In addition, if the treatment is inevitable, then factors such as teratogenesis, withdrawal symptoms, neurobehavioral effects, risk of untreated and risk of discontinuing the medication need to be considered before selecting the suitable therapy. Keywords: Pregnancy, Depression, Drug-therapy, Fetal toxicity